LONG-TERM LENALIDOMIDE MAINTENANCE IN MULTIPLE MYELOMA: EFIICACY AND MENAGEMENT OF RARE SIDE EFFECTS - A CASE REPORT - Sulejmani, Haris; Balkanov, Ivan; Zafirova, Ivana; Bogdanovski, Nenad; Oranska, Gordana; Balkanov, Svetlana Krstevska (Journal of Morphological Sciences, 2024)
The clonal growth of plasma cells in the bone marrow causes multiple myeloma (MM), a complicated blood cancer. This can lead to complications and myeloma-associated organ damage. Lenalidomide, an immunomodulatory drug, has made MM much more effective, especially in maintenance therapy after autologous stem cell treatment transplantation (ASCT). This case report describes a female patient with immunoglobulin G (IgG) type multiple myeloma who has been receiving ongoing therapy since her initial diagnosis. After receiving a diagnosis of multiple myeloma in 2015, the 51-year-old female underwent VTD regimen (Velcade,Thalidomide,and Dexamethason) four cycles,  an autologous stem cell transplant (ASCT), and two years of Velcade maintenance and bisphosphonate therapy for 6 months, which led to a complete remission. After  3 months of free therapy in  2018, the disease relapsed, prompting a switch to the VRD regimen (Velcade, Revlimid, and Dexamethasone), which resulted in a full response after four cycles. Subsequently, she experienced severe gastrointestinal manifestations, such as diarrhea, which were unresponsive to supportive care and basic anti-diarrheal medication. Consequently, we initiated treatment with colesevelam. In 2019, she underwent a second ASCT and recovered successfully. Serum electrophoresis and a PET/CT scan in 2023 identified active tonsils and lymph nodes but no new tumors. The patient is still in remission, undergoing maintenance therapy with Lenalidomide, and receiving regular monitoring. This case study highlights the complex problems of managing multiple myeloma, emphasizing the importance of individualized treatment regimens that include supportive care measures to mitigate side effects. Recent clinical studies indicate that colesevelam, a bile acid binder, efficiently reduces gastrointestinal symptoms associated with lenalidomide medication, thereby improving patient quality of life. By managing medication-related side effects like diarrhea and life-threatening complications like electrolyte imbalance, healthcare practitioners can help patients adhere to long-term treatment regimens, eventually improving clinical results and sustaining lenalidomide's therapeutic advantages. This paper emphasizes the need for a comprehensive strategy for managing multiple myeloma, including pharmaceutical and supportive therapy to promote patient well-being. Key words: Multiple Myeloma, Lenalidomide, Maintenance therapy, Colesevelam, Diarrhea, Autologous stem cell transplantation.